Research on fossil Chondrichthyes in Japan: current status and future - Takakuwa, Yuji (Fossils, 2021)
The research history of fossil Chondrichthyes in Japan has started more than 100 years ago. This paper presents an overview of the studies that have been published since the 1990s, and also advocates future perspective of research subjects of fossil Chondrichthyes in Japan based on the studies.The fossil record of Japanese chondrichthyans, which are mainly composed of elasmobranchs, is an important representative of the present Northwest Pacific region. Those from the Paleozoic (with part of the Triassic) include in limestone blocks within accretionary prisms of subduction zones in the main. They show the developmental process of elasmobranchs in the pelagic region during the Late Paleozoic and the Early Mesozoic. Those from the Mesozoic and Cenozoic are derived from normal clastic deposits. The fossil assemblages from these eras include some of few deep-sea species in the world and tooth sets from some species. These are important evidence of the chondrichthyan faunal transition of the Northwest Pacific region after the Mesozoic.In recent years, some of the fossil records that have passed time since their initial report need to be reclassified based on new taxonomy. Morphological studies on chondrichthyan fossils using CT scan, studies with chemical analyses and other advanced technological methods are also increased. On the other hand, many foreign specimens with high research potential are housed in domestic museums. It is hoped that further research on these foreign specimens and other domestic fossils, such as tooth sets, will reveal much about the evolution of chondrichthyans and the paleoecology of extinct species.